A novel photo-responsive europium(iii) complex for advanced anti-counterfeiting and encryption. Issue 13 (10th March 2016) - Mei, Jin-Feng; Lv, Zhong-Peng; Lai, Jian-Cheng; Jia, Xiao-Yong; Li, Cheng-Hui; Zuo, Jing-Lin; You, Xiao-Zeng
Abstract : By using light as external stimuli to modulate the multiple distinguishable identities of a novel photo-responsive europium(iii ) complex, advanced anti-counterfeiting and double encryption were realized. Abstract : A novel europium(iii ) complex simultaneously exhibiting photocolorimetric and photofluorometric behavior was obtained. Multiple distinguishable identities can be obtained and reversibly modulated using light as external stimuli. With this novel photo-responsive complex, double encryption and advanced anti-counterfeiting were realized.